Identity and Intervention: Disciplinarity as Transdisciplinarity in Gender Studies. (September 2015) - Pulkkinen, Tuija
Within the past 40 years, feminist studies/women's studies/gender studies/studies in gender and sexuality has effectively grown into a globally practised academic discipline while simultaneously resisting the notion of disciplinarity and strongly advocating multidisciplinarity, interdisciplinarity, and transdisciplinarity. In this article, I argue that gaining identity through refusing an identity can be viewed as being a constitutive paradox of gender studies. Through exploring gender studies as a transdisciplinary intellectual discipline, which came into existence in very particular multidisciplinary historical conditions of the feminist movement, I suggest that transdisciplinarity within gender studies takes on a meaning which results in a radical problematization of the academic goal of 'knowledge production'. Instead of such 'knowledge production', transdisciplinarity in gender studies promotes intervention which reaches beyond the concepts of accountability, innovation and corporate management. I argue that Jacques Derrida's promotion of the Collège International de Philosophie in 1982 in its particular relationship to the tradition of philosophy provides a parallel example of such an attitude. Adding to Joan Scott's and Clare Hemmings's insights on gender studies in terms of critique and transformation, I argue that transdisciplinarity as practice of 'intervention' is crucial for the construction of gender studies disciplinary identity, based upon apparent non-identity.